2010
DOI: 10.1128/jvi.01417-10
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus Infection Induces Autophagy-Like Vesicles and Megaphagosomes in Pancreatic Acinar Cells In Vivo

Abstract: Autophagy can play an important part in protecting host cells during virus infection, and several viruses have developed strategies by which to evade or even exploit this homeostatic pathway. Tissue culture studies have shown that poliovirus, an enterovirus, modulates autophagy. Herein, we report on in vivo studies that evaluate the effects on autophagy of coxsackievirus B3 (CVB3). We show that in pancreatic acinar cells, CVB3 induces the formation of abundant small autophagy-like vesicles and permits amphisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
184
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(207 citation statements)
references
References 98 publications
(98 reference statements)
22
184
1
Order By: Relevance
“…Additionally, we found that CVB readily infects BeWo cells and forms characteristic double-membrane replica-tion complexes in BeWo trophoblasts (Fig. 1D), similar to those detected in other cell types following picornavirus infection (46)(47)(48). These data reveal that BeWo trophoblasts are an appropriate polarized cell model for studying CVB interactions at the maternal-fetal interface.…”
Section: Resultssupporting
confidence: 75%
“…Additionally, we found that CVB readily infects BeWo cells and forms characteristic double-membrane replica-tion complexes in BeWo trophoblasts (Fig. 1D), similar to those detected in other cell types following picornavirus infection (46)(47)(48). These data reveal that BeWo trophoblasts are an appropriate polarized cell model for studying CVB interactions at the maternal-fetal interface.…”
Section: Resultssupporting
confidence: 75%
“…6). Indeed, features of impaired autophagy are evident in human disease (3,43,111) and in all experimental models of pancreatitis (1,7,55,65,77,108), including those induced by ethanol ϩ LPS (24) or coxsackievirus infection (51). The lysosomal/autophagic disordering is an early event in development of the disease.…”
Section: Role Of Lysosomal and Autophagic Dysfunction In Pancreatitismentioning
confidence: 99%
“…Certain picornaviruses, including poliovirus (PV), coxsackievirus, and enterovirus 71 subvert the autophagic pathway to generate double-membraned vesicles, which are thought to serve as substrates for viral genome replication (9,10,12,28). Increased autophagy has a positive effect on PV replication, and PV, human rhinovirus 2 (HRV-2), and HRV-14 induce autophagosome formation, based on a single assay analyzing colocalization of LC3 and the lysosome/endosome marker LAMP1 (10).…”
mentioning
confidence: 99%